Hexahydrated Mg(2+) Binding and Outer-Shell Dehydration on RNA Surface - Yu, Tao (Biophys J, 2018)
The interaction between metal ions, especially Mg(2+) ions, and RNA plays a critical role in RNA folding. Upon binding to RNA, a metal ion that is fully hydrated in bulk solvent can become dehydrated. Here we use molecular dynamics simulation to investigate the dehydration of bound hexahydrated Mg(2+) ions. We find that a hydrated Mg(2+) ion in the RNA groove region can involve significant dehydration in the outer hydration shell. The first or innermost hydration shell of the Mg(2+) ion, however, is retained during the simulation because of the strong ion-water electrostatic attraction. As a result, water-mediated hydrogen bonding remains an important form for Mg(2+)-RNA interaction. Analysis for ions at different binding sites shows that the most pronounced water deficiency relative to the fully hydrated state occurs at a radial distance of around 11 Å from the center of the ion. Based on the independent 200 ns molecular dynamics simulations for three different RNA structures (Protein Data Bank: 1TRA, 2TPK, and 437D), we find that Mg(2+) ions overwhelmingly dominate over monovalent ions such as Na(+) and K(+) in ion-RNA binding. Furthermore, application of the free energy perturbation method leads to a quantitative relationship between the Mg(2+) dehydration free energy and the local structural environment. We find that [Formula: see text] the change of the Mg(2+) hydration free energy upon binding to RNA, varies linearly with the inverse distance between the Mg(2+) ion and the nearby nonbridging oxygen atoms of the phosphate groups, and [Formula: see text] can reach −2.0 kcal/mol and −3.0 kcal/mol for an Mg(2+) ion bound to the surface and to the groove interior, respectively. In addition, the computation results in an analytical formula for the hydration ratio as a function of the average inverse Mg(2+)-O distance. The results here might be useful for further quantitative investigations of ion-RNA interactions in RNA folding.